2023
DOI: 10.1002/ajb2.16109
|View full text |Cite
|
Sign up to set email alerts
|

Flowers that self‐shade reduce heat stress and pollen limitation

Abstract: Premise: Plants are facing increased risk of heat stress with global climate change.Reproductive tissues are particularly heat-sensitive, which can result in lower plant fitness. Floral shading and closure are possible mechanisms to limit heat stress although most previous work on petal orientation has considered adaptations to raise temperatures. We hypothesized that floral shading could reduce temperature and increase reproductive success. Methods: We measured floral temperatures of four species that exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…The finding that flowerheads of C. corymbosa undergo a regular diel rhythm of internal refrigeration raises questions about the mechanism permitting these plants to periodically cool their flowers in the torrid weather that prevails during its flowering season, but also on the possible costs and benefits associated with the species' floral thermal biology. Regarding the possible cooling mechanism, reduced solar irradiance inside these flowerheads due to self‐shading (Karban et al, 2023) can be safely ruled out, since substantial thermal deficits persisted also for most of the night (Figure 2). The most parsimonious hypothesis is that periodic flowerhead cooling in C. corymbosa was achieved by temporarily enhanced transpiration in the florets and/or receptacle.…”
Section: Figurementioning
confidence: 99%
“…The finding that flowerheads of C. corymbosa undergo a regular diel rhythm of internal refrigeration raises questions about the mechanism permitting these plants to periodically cool their flowers in the torrid weather that prevails during its flowering season, but also on the possible costs and benefits associated with the species' floral thermal biology. Regarding the possible cooling mechanism, reduced solar irradiance inside these flowerheads due to self‐shading (Karban et al, 2023) can be safely ruled out, since substantial thermal deficits persisted also for most of the night (Figure 2). The most parsimonious hypothesis is that periodic flowerhead cooling in C. corymbosa was achieved by temporarily enhanced transpiration in the florets and/or receptacle.…”
Section: Figurementioning
confidence: 99%
“…At the reproductive stage in flowering plants, floral temperature can have important consequences for gamete development and viability (Thakur et al 2010;Zinn et al 2010;Hedhly 2011), pollination (Norgate et al 2010), and fertilization (Cerovi c et al 2000). Plants have evolved a variety of mechanisms that modify floral temperature, including heliotropism (Zhang et al 2010), thermogenesis (Watling et al 2008;Seymour et al 2009), evaporative cooling (Galen 2006), shading of reproductive structures (Karban et al 2023), and the focus or reflection of solar radiation (Kevan 1975;McKee & Richards 1998). While some of these mechanisms (e.g., heliotropism) are likely adaptive (Creux et al 2021), others, such as transpirational cooling, may result from plant-wide physiological responses to ambient temperature that incidentally impact floral temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of evaporative cooling may enhance both seed and pollen performance in some taxa (Patiño & Grace 2002). Recent work has shown that petal positioning over reproductive structures in a suite of Californian taxa can reduce floral temperature, with positive consequences for seed production (Karban et al 2023). Furthermore, some bees have been shown to 'overheat' within warm flowers and take cooling flights (Corbet & Huang 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation